Upaya Sekolah Dalam Meningkatkan Prestasi Non Akademik Siswa Melalui Manajemen Sarana Prasarana Di SMP Muhammadiyah Boarding School Pleret - Safinatun Munawaroh; Rz. Ricky Satria Wiranata (STAI Terpadu Yogyakarta, 2020)
This research aims to determine: (1) how the management of infrastructure facilities in SMP Muhammadiyah Boarding School Pleret, (2) how the school's efforts to improve student non-academic achievement through the management of infrastructure facilities at SMP Muhammadiyah Boarding School Pleret. The research method used is a qualitative case study method. The research subject is the principal. Meanwhile, the research informants were the deputy principal of the school for facilities and infrastructure, the vice principal of the curriculum section, the extracurricular coordinator, administrative staff, homeroom teachers, and students. The conclusions of the results of this study indicate that: Management of infrastructure facilities carried out at SMP Muhammadiyah Boarding School Pleret, namely planning, procurement, use, storage, and maintenance. The school's efforts to improve student non-academic achievement through renewal and provision of extracurricular infrastructure. Schools make various other efforts, such as providing the best coaches to hone student talents, finding competent teachers, and actively facilitating students to participate in various competitions. Ustadz / ah provide good mentoring and guidance so that students can be enthusiastic and earnest in achieving.